Aesthetic results following breast cancer surgery: A prospective study on 6515 cases from ten Italian Senonetwork breast centers. Issue 10 (October 2020) - Serra, M.; Li, A. Quattrini; Cataliotti, L.; Cianchetti, E.; Corsi, F.; De Vita, R.; Fabiocchi, L.; Fortunato, L.; Friedman, D.; Klinger, M.; Marotti, L.; Murgo, R.; et al.
Abstract: Breast cancer treatment has deeply changed in the last decades, since clinical and oncological cure cannot be achieved without patient's satisfaction in term of aesthetic outcomes. Several methods have been proposed to objectively assess these results. However, Italian breast centers have not yet agreed on measurable, reproducible and validated aesthetic outcome indicators to monitor their performance. Methods: The study was designed and conducted by Senonetwork, a not-for-profit association of Italian breast centers. Ten breast centers were selected based on specific eligibility criteria. This multicentre observational prospective study recruited 6515 patients with diagnosis of in situ or invasive breast cancer who underwent breast surgery in the years 2013–2016. Thirteen indicators of aesthetic results and of related quality of care were analyzed. Data collection and analysis were conducted using a common study database. Results: On average, seven out of ten centers were able to collect data on the proposed indicators with a proportion of missing values < 25%. By expert consensus based on study results, some seven indicators have been defined as "mandatory" while the remaining six have been defined as "recommended" because they require further refinement before they can be proposed for monitoring aesthetic outcomes or because there are doubts on the feasibility of data collection. The minimum standard is reached for 5 of 13 indicators. This finding and the wide range between centers reveal that there is ample room for improvement. Conclusions: From the present study useful measurable aesthetic parameters have emerged, leading to the definition of target objectives that breast centers can use for benchmarking and improvement of quality of care.